2014
DOI: 10.1158/1535-7163.mct-13-0466
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Sphingosine Kinase Induces Apoptosis and Tumor Regression for KSHV-Associated Primary Effusion Lymphoma

Abstract: Sphingosine kinase (SphK) is overexpressed by a variety of cancers, and its phosphorylation of sphingosine results in accumulation of sphingosine-1-phosphate (S1P) and activation of anti-apoptotic signal transduction. Existing data indicate a role for S1P in viral pathogenesis, but roles for SphK and S1P in virus-associated cancer progression have not been defined. Rare pathologic variants of diffuse large B-cell lymphoma arise preferentially in the setting of HIV infection, including primary effusion lymphoma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
89
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(93 citation statements)
references
References 53 publications
1
89
3
Order By: Relevance
“…We have previously shown that several small-molecule compounds induced by PEL apoptosis are connected to reactivate KSHV lytic gene expression. 30,31 However, here we only found a slight increase of viral latent/lytic gene expression (but with no statistical significance) within PF-2341066-treated BCBL-1 cells (supplemental Figure 2).…”
Section: Kshv Activates the Hgf/c-met Pathway In Vitro And In Vivocontrasting
confidence: 52%
“…We have previously shown that several small-molecule compounds induced by PEL apoptosis are connected to reactivate KSHV lytic gene expression. 30,31 However, here we only found a slight increase of viral latent/lytic gene expression (but with no statistical significance) within PF-2341066-treated BCBL-1 cells (supplemental Figure 2).…”
Section: Kshv Activates the Hgf/c-met Pathway In Vitro And In Vivocontrasting
confidence: 52%
“…ABC294640 was found to reduce pro-proliferative signalling through the Akt and MAPK pathways via reduction in S1P receptor signalling. More recent studies with ABC294640 have implied roles for SK2 in regulating autophagy [119], transcription of key cancer-promoting genes such as c-Myc [36,98] and pro-inflammatory mediators through NF-κB [120][121][122][123]. ABC294640 also induced proteasomal degradation of SK1 and Des1 [80], Myc and other targets such as androgen receptor [53,98] and Mcl-1 [37] through an as yet undetermined mechanism that appears to be related to its ability to inhibit Des1 [80].…”
Section: Abc294640mentioning
confidence: 99%
“…ABC294640 has been used extensively in vivo where it has shown some efficacy in animal models of solid tumours [50,98,113,114,116,118,124,125], blood cancers [36,37,121], and inflammatory conditions such as osteoarthritis [126], transplantation [120], stroke/ischemia [122,127] and colitis [128,129] (Table 2). It has been shown to dose-dependently decrease circulating S1P in mice [50] and S1P levels in xenograft tumours [50,112].…”
Section: Abc294640mentioning
confidence: 99%
“…The binding of S1P to hTERT prevents its interaction with makorin ring finger protein 1 (MKRN1), 115 an E3 ubiquitin ligase that polyubiquitinates hTERT and promotes its proteasomal degradation (see 116 6 for details).…”
mentioning
confidence: 99%